Dynamic phonon manipulation by optomechanically induced strong coupling between two distinct mechanical resonators - Huang, Jianguo (2020)
Optical information storage is essential for optical and quantum computation and communication, which can be implemented with various media including atoms, ions, and phonons. The main challenge lies in implementing a robust control to drastically slow down, store and transport ultrafast optical signals. Cavity optomechanics enable information storage by converting photons into acoustic phonons in mechanical resonators. However, fast and controllable effective coupling between multiple mechanical resonators remains elusive for dynamic phonon manipulation and information transfer. This study considers dynamic phonon manipulation via optomechanically induced strong coupling between two distinct mechanical resonators. When the two resonators within an optical cavity are excited to optomechanical self-oscillation, strong coupling is observed when a parametric pump laser compensates for their mechanical frequency mismatch. The strong and controllable coupling between the mechanical resonators demonstrated on the fully integrated nanoscale optomechanical device is promising for dynamic phonon manipulation and robust optical information storage.